PARTISIPASI ANGGOTA KELOMPOK WANITA TANI LANGGENG MAKMUR DALAM PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) DI DESA JATIREJO KECAMATAN LENDAH KABUPATEN KULON PROGO - Rianja Rianja; Ign Suprih Sudrajat; Eska Stefani (Fakultas Pertanian UST, 2025)
This study aims to analyze the level of participation of members (KWT) Langgeng Makmur in the (KRPL) Program and analyze the factors that influence the participation of members (KWT) Langgeng Makmur in the (KRPL) Program. The basic method used in the study is the quantitative method. The sampling method employs a census, specifically targeting all 30 members of KWT Langgeng Makmur. The analysis method uses a Likert scale to calculate the level of participation and analysis using multiple linear regression. The results of the study of the level of participation in planning were 57% (moderate category), participation in implementation was 63.44% (high category), participation in monitoring and evaluation was 58.33% (moderate category), and participation in utilization of results was 55.73% (moderate category). The results of the T test of the characteristic variable are -1.216 <T table of 2.052, meaning that the characteristic variable does not affect the level of participation. The results of the T-test of the farmer's ability variable are 4.180> T table 2.052, meaning that the farmer's ability variable affects the level of participation. The calculated F test is 11.414 > 3.35 (f table), then the characteristics and farmer capabilities variables simultaneously influence participation. The R2 test is 0.418, which means that the influence of the independent variable or X, on the dependent variable Y is 0.418, while the remaining 0.582 is influenced by other variables.